Evaluating the Impact of Public Policies to Support Small Businesses: - Storey, David J. (Senate Hall, 2003)
Virtually all developed economies utilize taxpayer's money to provide either free or subsidized assistance to small businesses, the self-employed or to potential small business owners. This paper provides an outline methodology for evaluating the impact of these policies. It identifies six approaches, beginning with the most simple and ending up with the most sophisticated. These are referred to as the 'Six Steps', with step Six being viewed as 'best practice' or 'heaven' in this area.
Keywords: small business|public policy